Abbreviated Goal Management Training Shows Preliminary Evidence as a Neurorehabilitation Tool for HIV-associated Neurocognitive Disorders among Substance Users. Issue 1 (2nd January 2016) - Casaletto, Kaitlin B.; Moore, David J.; Woods, Steven Paul; Umlauf, Anya; Scott, J. C.; Heaton, Robert K.
Abstract : Objective : Substance use disorders are highly comorbid with and contribute to the increased prevalence of neurocognitive dysfunction observed in HIV infection. Despite their adverse impact on everyday functioning, there are currently no compensatory-based neurorehabilitation interventions validated for use among HIV+ substance users (HIV/SUD). This study examined the effectiveness of goal management training (GMT) alone or GMT as part of a metacognitive training among HIV/SUD individuals with executive dysfunction. Methods : Ninety HIV/SUD individuals were randomized to a single 15-min session: (1) GMT ( n = 30); (2) GMT plus metacognitive training (neurocognitive awareness; GMT + Meta; n = 30); or (3) active control ( n = 30). Following a brief neurocognitive battery and study condition, participants performed a complex laboratory-based function task, Everyday Multitasking Test (Everyday MT), during which metacognition (awareness) was evaluated. Results : There was an increasing, but non-significant tendency for better Everyday MT performances across study conditions (Control ≤ GMT ≤ GMT + Meta; ps < .08). Post hoc analyses showed that GMT and GMT + Meta groups demonstrated small benefits ( d = .20–.27) compared to the control arm but did not differ from one another ( ds < .10). When GMT groups were combined, there were significant medium effect size benefits in Everyday MT performance and metacognitive task appraisals as compared to the control condition. Among participants who underwent GMT, benefits were most prominent in persons with poorer pre-training dual-tasking ability, depression, and methamphetamine use disorders ( ds = .35–1.04). Conclusions : A brief compensatory strategy has benefits for everyday multitasking and metacognition among HIV+ substance users with executive dysfunction. Future work exploring more intensive trainings, potentially complimentary to other restorative approaches and/or pharmacological treatments, is warranted.